Capital accumulation, green paradox, and stranded assets: An endogenous growth perspective - Wei Jin; ZhongXiang Zhang (Fondazione Eni Enrico Mattei (FEEM), 2018)
The existing studies on Green Paradox and stranded assets focus on dirty exhaustible assets (fossil fuel reserves) and show that environmental regulations, by changing the costs of dirty inputs relative to clean ones, lead to replacements of the former by the latter and stranding of dirty assets due to perfect substitution. It, in turn, induces acceleration of dirty resource extractions and pollution emissions for fear of dirty assets becoming stranded - the Green Paradox effect. This paper uses an endogenous growth framework to revisit the problem of Green Paradox and stranded assets by taking a new perspective that focuses on capital accumulation with investment irreversibility. We show that if 1) direct irreversibility of investment does not rule out the indirect channel of converting dirty capital goods into clean ones through final goods allocations, and 2) interactions between dirty and clean capital as imperfect substitutes can generate reciprocal effects, then environmental regulation, through directing investment towards clean capital, does not necessarily leads to asset stranding of dirty capital. Accumulation of clean capital with a pollution-saving effect offsets the polluting impact of dirty one and leads to reversed Green Paradox. We further propose an endogenous growth mechanism through which the accumulation of both dirty and clean capital, as well as environmental improvement, can be sustained in the long run without converging to the steady state.
Keywords: Q54; Q43; Q32; O13; O44; C61; 330; Endogenous Growth; Green Paradox; Stranded Assets; Capital Accumulation; Imperfect Substitution; Investment Irreversibility